Students' Critical Thinking Ability in Class X Economics Learning at MAN KOTIM - halimah, Siti halimah; Julianta, Ifan; Astuti, Neneng Mardi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aim of the research is to find out how students' critical thinking skills are when learning economics at Madrasah Aliyah Negeri (MAN) East Kotawaringin for the 2022/2023 academic year. The problem with this research is that students are less interested in exploring the explanations of the economic learning material presented by the teacher. Students have difficulty explaining the material practically.The design used in this research is qualitative descriptive research. The subjects of this research were class X IPS students at MAN East Kotawaringin for the 2022/2023 academic year. Subjects used a purposive sampling technique, taking data sources using certain considerations and using simple random sampling.he results of the research include that the critical thinking skills of class Students have demonstrated their critical thinking skills in learning as seen from the results of interviews conducted by the author with students regarding the test questions that have been given.